Hume's skeptical crisis a textual study - Fogelin, Robert J. (New York ; Oxford : Oxford University Press, 2009)
'Hume's Skeptical Crisis' is a textual study of the shifts in perspective that unfold as Hume attempts to produce a complete science of human nature. In the process, Hume's standpoint shifts from buoyant optimism to profound skeptical melancholy and finally comes to rest at a stable form of mitigated skepticism.
Description based on print version record.
Keywords: Hume, David, -- 1711-1776.; Skepticism; Knowledge, Theory of